Reforming Islamic Finance: A Framework for a Proposed Non-Banking Institution to Facilitate Participative Financing - Khalid Rashid (Department of Sharia Economic Law, Faculty Sharia and Law, UIN Sunan Gunung Djati Bandung, 2026)
This article addresses a key issue in Islamic banking, namely, the limited use of participative financing and the overwhelming reliance on debt-based instruments. Islamic banks avoid participative financing due to adverse selection and moral hazard risks. While the literature emphasizes greater use of PLS-based participative financing, it does not offer practical solutions for the challenges that Islamic banks encounter in its implementation. This study employs a conceptual and analytical methodology, drawing on theoretical reasoning and professional insights to examine Islamic banking practices. It reviews Islamic finance literature and industry practices to identify the challenges banks face in implementing participative financing. The study highlights that Islamic banks are not structured to manage issues of adverse selection and moral hazard. This study presents, as its main outcome, a framework for a new non-banking institution specifically designed for participative financing. The pre-investment and post-investment services offered by the proposed institution are designed to mitigate the risks of adverse selection and moral hazard. The article concludes with an emphasis on the need to initiate the development of such institutions, even on a small scale. It argues that with persistent improvements, these institutions can evolve into sustainable entities that will significantly contribute to the implementation of Islamic finance, both in its form and substance. Due to its conceptual nature, the study does not provide empirical validation of the proposed framework. Future research may assess the practical viability of the proposed institution and its effectiveness in mitigating the related risks.